The philosophy of translation - Searls, Damion (Yale University Press, 2024)
"Avoiding theoretical debates and clichéd metaphors, award-winning translator Damion Searls has written a fresh, approachable, and convincing account of what translation really is and what translators actually do. As the translator of sixty books from multiple languages, Searls has spent decades grappling with words on the most granular level: nouns and verbs, accents on people's names, rhymes, rhythm, untranslatable cultural nuances. Here, he connects a wealth of specific examples to larger philosophical issues of reading and perception. Translation, he argues, is fundamentally a way of reading--but reading is much more than taking in information, and translating is far from a mechanical process of converting one word to another. This sharp and inviting exploration of the theory and practice of translation is for anyone who has ever marveled at the beauty, force, and movement of language."
Keywords: Übersetzungswissenschaft; Translating and interpreting / History; Translators / Case studies